Characterization of a rat orthotopic pancreatic head tumor model using three‐dimensional and quantitative multi‐parametric MRI. (23rd December 2016) - Yin, Ting; Peeters, Ronald; Feng, Yuanbo; Liu, Yewei; Yu, Jie; Dymarkowski, Steven; Himmelreich, Uwe; Oyen, Raymond; Ni, Yicheng
Abstract : The purpose of this study was to investigate the reliability of 3D isotropic MRI and quantitative multi‐parametric MRI characterization on an orthotopic pancreatic head tumor model in rats. 3D isotropic T 2 ‐weighted MRI was performed as a routine for tumor longitudinal follow‐up and volume estimation. Common bile duct diameter was measured from 3D multiplanar reconstruction. Quantitative multi‐parametric measurements including pixel‐wise T 2, T 1 relaxivity, apparent diffusion coefficient (ADC) and apparent diffusion kurtosis mapping were performed twice throughout tumor growth. Semi‐quantitative and quantitative analyses based on an extended Tofts model were applied to region‐of‐interest‐based dynamic contrast‐enhanced imaging, followed by contrast ratio measurement on standard contrast‐enhanced imaging. Moreover, low‐level texture‐based analysis was inspected for T 2, T 1, ADC and contrast ratio measurements. Results indicated that multi‐parametric MRI showed good reproducibility for tumor characterization; the measurements were not affected by tumor growth. Tumor growth was further confirmed with histology examinations. To conclude, state‐of‐the‐art clinical MRI techniques were translated to this preclinical tumor model with high reliability, and have paved the way for translational oncology studies on this tumor model. Abstract : An orthotopic pancreatic head tumor model in rats was established with high reproducibility. This model has been further characterized by 3D isotropic and multi‐parametric MRI methods (T1, T2 relaxivity mapping, DWI, DKI and DCE) for possible quantitative assessment. The reliability of tumor characterization on MRI was not affected by tumor growth.